Analisis Komparasi Pengaruh Model AIDA Terhadap Keputusan Nasabah Menggunakan Produk Cicilan Emas Pada Dua Kantor Cabang Bank Syariah Mandiri - Damayanti Achmad Suroko; Ambardi Ambardi; Mukhaer Pakkanna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2020)
The development of the Indonesian sharia banking industry approved this in a positive direction. In Indonesia, Islamic banks independently are still the most widely seen Islamic banks in terms of assets owned. Gold Installment Product is one of the products issued by Bank Syariah Mandiri, where this product is a bank facility as gold ownership for the community or the community. One model that is often used to measure consumer decisions in choosing a product is the AIDA model (Attention, Interests, Desires, Actions). This model talks about the various phases that consumers go through before they decide to buy a product or service. Some marketers follow this model to capture more consumers for their products The purpose of this study is to analyze the decision regarding the AIDA factor model of the purchase decision in gold installment products between Bank Syariah Mandiri Mayestik Branch and Kebun Jeruk branch In this study using quantitative analysis methods. This research was conducted in two places, namely Bank Syariah Mandiri branch office Mayestik branch and Kebun Jeruk branch. In this study the data collection technique was carried out by using a questionnaire survey method. While the technique of taking samples in this study using non-probability sampling technique is purposive sampling type. To analyze the influence, interests, desires, actions in each branch office using the F test and t test. From the results of this study it can be concluded that the Mayestik branch office is a significant influence of the AIDA model on the decision to use gold installment products. While in the orange orchard branch office does not have a significant influence on the decision to use gold installment products.